Compatibility of Orius insidiosus (Hemiptera: Anthocoridae) with Amblyseius swirskii (Acari: Phytoseiidae) for control of Flankliniella occidentalis (Thysanoptera: Thripidae) in pepper - Maria Eugenia Lorenzo Larregui; Leticia Bao; Gabriela Grille; Luciana Mendez; Oliver Bonato; César Basso (Agrociencia Uruguay, 2021)
Biological control programs in greenhouses increasingly resort to the release of several natural enemies simultaneously. In Uruguay, pest management in peppers is based on the release of Orius insidiosus and Amblyseius swirskii, to control Frankliniella occidentalis and Bemisia tabaci. Amblyseius swirskii can feed on both preys. Zoophytophagous predators not only feed on pests or plant food, but also on natural enemies with which they share prey (intraguild predation). Hence, the combined release of generalist predators could have a negative result in the control of the target pest. Thus, it was important to evaluate the compatibility of O. insidiosus and A. swirskii as predators of F. occidentalis. Studies carried out at Petri dishes level assessed: (1) the effect of the density and the composition of the prey on their predation by O. insidiosus, (2) the change of prey by O. insidiosus and (3) the effect of the genus of O. insidiosus on prey preference. Results show that if the relative densities of F. occidentalis and A. swirskii varied, O. insidiosus always changed to the most abundant prey. Male and female O. insidiosus preferred nymphs of F. occidentalis over A. swirskii, and females killed more prey than males. Since O. insidiosus fed on A. swirskii, it is advisable to be cautious when combining anthocorids and phytoseid mites for the F. occidentalis control. Studies at greenhouse will be necessary to clarify the final effect of both predators.